2020
DOI: 10.3390/ma13194465
|View full text |Cite
|
Sign up to set email alerts
|

Surface Evaluation of a Multi-Pass Flexible Magnetic Burnishing Brush for Rough and Soft Ground 60/40 Brass

Abstract: Burnishing is an advanced finishing process that produces higher-quality surfaces with better hardness and roughness than conventional finishing processes. Herein, a flexible magnetic burnishing brush comprising stainless steel pins under permanent magnet poles was used to investigate the influence of multiple passes and directions on the produced surface of soft and rough ground prepared brass. In total, five different samples were burnished on each of the two brass samples prepared. Four samples were process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…Only one exception occurred at a speed of 1250 rpm, where the highest microhardness average was observed at a low feed rate of 6 mm min −1 ; it also exerted the optimum condition among all the tested conditions. The results of this study conform to those of previous studies that have reported an increase in hardness values on the deformed layer of materials treated by shot peening [27], the waterjet peening process [28], ultrasonic cavitation modification [29], flexible magnetic burnishing brush [20,21], and the ultrasonic surface rolling process [30].…”
Section: Microhardnesssupporting
confidence: 91%
See 1 more Smart Citation
“…Only one exception occurred at a speed of 1250 rpm, where the highest microhardness average was observed at a low feed rate of 6 mm min −1 ; it also exerted the optimum condition among all the tested conditions. The results of this study conform to those of previous studies that have reported an increase in hardness values on the deformed layer of materials treated by shot peening [27], the waterjet peening process [28], ultrasonic cavitation modification [29], flexible magnetic burnishing brush [20,21], and the ultrasonic surface rolling process [30].…”
Section: Microhardnesssupporting
confidence: 91%
“…They showed that the burnishing speed and feed rate determine the surface quality and homogeneity, improving the microhardness by 40%, microroughness by 76%, and corrosion rate at a certain range of speed and feed rate. Alaskari et al [ 21 ] examined the influences of multi passes and directions of FMBB on different initial brass surface conditions at a fixed optimum speed and feed rate. They proved that the initial surface roughness, number of passes, and reverse strain mechanism primarily affect the surface properties and integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Burnishing is one of the methods of finishing metals and their alloys, sinters and plastics, which involves the use of local plastic deformation [1][2][3], generated in the surface layer of the object [4][5][6][7][8][9], as a result of specific (force and kinematic) interaction of hard and a smooth tool (in the shape of a ball, disc, roller or other) with a machined surface [10][11][12][13][14][15][16][17][18]. The surface state and quality after previous treatment significantly depend on its quality after previous treatment [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Jordi Llumà et al proved that an increase in burnishing preload diminishes the ductile behavior of the material and increases its strength representative values, although the proportion of affected material in the cross-section of the specimen is reduced with regard to the whole surface. The influence of multiple passes and directions on the produced surface of soft and rough ground-prepared brass was recommended by Alaskari [10]. The surface after-slide burnishing parameters on the surface roughness of shafts were tested using the artificial neural networks with the best regression statistics, which predicted an average surface roughness of the shafts with R 2 = 0.987 [11].…”
Section: Introductionmentioning
confidence: 99%